Donald Trump dan Reorientasi Kebijakan Keamanan Amerika Serikat Terhadap Program Pengembangan Senjata Nuklir Korea Utara. - Al Syahrin, Muhammad Najeri (Parahyangan Center for International Studies, 2018)
This research attempts to identify some of the trends in changing the orientation of Donald Trumps and United States security policies toward North Koreas nuclear weapons development program. The identification begins with an explanation of some of the strategic and policy options that have been done and have not yet by the United States in an effort to stop nuclear tensions in the East Asian region. After describing some of the policy options for Donald Trump, this study will predict the right security policy in the denuclearization of the Korean peninsula. The Trump policy is expected to show greater urgency than the previous United States presidential policy. Based on the assumption, through